The Imantodes (Serpentes: Colubridae) of Costa Rica: Two or three species? - Savage, Jay M. (1985)
Imantodes inornatus and Imantodes cenchoa are currently recognized as occurring in Costa Rica. It has been suggested recently that I. cenchoa is actually a composite of two species, I. cenchoa and I. gemmistratus. AnaIysis of data on scalation and coloration for Costa Rican samples confirms that this complex is comprised of two species. One of these is clearly the wide-ranging I. cenchoa, which in Costa Rica occurs in the southwest Pacific Lowlands, Meseta Central, Atlantic lowlands and cordilleran slopes and just on to the Pacific slope in the northern mountains. It does not range into the northwestern (Pacific) lowlands. A second species occurs on the northwestern Pacific lowlands and in sympatry with cenchoa on the Meseta Central and at scattered localities in the Atlantic and southwest Pacific lowlands. The second form is allopatric to Panamanian gemmistratus and consistently differs from the latter in scalation. A review of other Central American and Mexican samples referred to I. gemmistratus (type locality: El Salvador: Sonsonate: near Volcan de Izalco) indicates that Costa Rican examples are conspecific with it. The species appears to be comprised of three allopatric subpopulations along the Pacific versant: El Salvador-Honduras; Nicaragua-Costa Rica; and Panamá. A fourth more or less allopatric subpopulation occurs on the Atlantic versant of Costa Rica as well.The systematic status of allopatric eastern México and Yucatán Peninsula populations referred by recent authors to gemmistratus is problematic. Other allopatric Isthmus of Tehuantepec and western México populations seem more likely candidates to be conspecific with gemmistratus, but the issue cannot be resolved on the basis of available data. Attention is called to a unique unicolor variant of gemmistratus from Pacific versant Costa Rica. lmantodes inornatus and cenchoa are restricted to evergreen- forest habitats, while gemmistratus is most abundant in deciduous forests along the west coast of Central America and Mexico. The latter species is sometimes found at evergreen forest sites on the Atlantic versants of Costa Rica and Central Panama. l. cenchoa and gemmistratus are known to be sympatric at several sites in Costa Rica but not I. inornatus and the Iatter species. I. cenchoa and inornatus are often taken together.